LEVELS OF MINERALS, VITAMIN AND POWER RECEIVED IN DRINK INFUSED WATER WITH DIVERSIFICATION - Surati Surati; SY. Didik Widiyanto; Nurul Qomariyah; Ririh Jatmi Wikandari (Jurnal Riset Kesehatan, 2019)
Infused water is drinking water that has been given additional pieces of fruit so that the water gives a certain sensation of water. Infused water are consumed by the community because the manufacturing process is easy and use local fruits. To determine the vitamin content (A and C), mineral content (K, Ca, Mg) and acceptability of infused water with sample codes (A, B and C). The benefits of this study are to be able to add to the list of healthy and nutritious drinks that are beneficial for health because infused water contains vitamins and minerals. Experiments with Complete Random Design (CRD), Sample code A, B and C in the analysis of vitamin levels, mineral content and acceptability. Acceptance analysis was carried out Friedman test and Wilcoxon test. Vitamin and mineral levels were analyzed by ANOVA and LSD statistics. Infused water contains mineral potassium, calcium and magnesium and contains vitamins A and C, there are significant differences between the sample code A, B and C. Infused water containing minerals, vitamins, and accepted by the community.